Justiça restaurativa e medida protetiva de reeducação: um estudo de caso sobre o Projeto Regando Flores - Gomes, Marianna de Queiroz (2020)
It aims to evaluate the potential of reeducation programs as a practice of restorative justice and in addressing domestic violence. It uses an exploratory literature review methodology as a way of exposing analysis premises, and then develops qualitative research with an inductive content, based on the collection of interviews with men and women included in the intervention program, staff and civil servants. Judiciary involved. It presents the criminal issue as a crisis in the contemporary justice system. It presents the penal paradigm of restorative justice as opposed to the retributive penal paradigm. It seeks the genealogy of restorative justice through the genealogy of the term and its theoretical origins. It exposes theoretical and social antecedents of restorative justice. Comments on various concepts of restorative justice, elements and subjects, from foreign scholars. Describes the minimalist and maximalist conceptions of restorative justice. It studies the concepts of the restorative paradigm in Resolution 2002/12 / UN and Resolution 225/2016 / CNJ. Investigates models of restorative practice. It presents impacts of domestic violence, on a personal, family and social level. It exposes domestic violence in an ecological focus, according to WHO, as it is both a public health problem and a question of denial of human rights, interconnected phenomena. It introduces the modern construction of the concept of violence. It investigates violence against women from Galtung and Bourdieu, treating it on three levels with feedback, physical, cultural and structural violence. Describes male domination in Bourdieu and its cultural consequences. It studies types of violence against women in international reference documents, comparative and Brazilian legislation. It exposes the origins of patriarchy, from the cultural formation of Brazil. It discusses the role of the State, family and school in the replication of gender violence. It presents contemporary patriarchy. It deals with the waves of the feminist movement and its merit on publicizing the private space. It discusses the human rights of women and the context of regulation of the Maria da Penha Law. Address the public policy of protection of the Maria da Penha Law, the feminism contained in the norm and the question of its effectiveness. It analyzes the legality of the aggressors' re-education program, taken as a way of transforming domestic conflict, starting from the disruption of the cycle of conjugal violence. It investigates the political significance of human rights education through criminal proceedings, taking the theoretical frameworks of the symbolic constitutionalization of Marcelo Neves and judicial democracy in Antoine Garapon. Describes the Regando Flores Project, its methodology, data collected and results achieved. Address violence based on peacebuilding, pedagogy of coexistence, education in human rights and peace circles. It gives zero recurrence about those involved in the project and positive results about the practice, before those involved and the community. Studies the intervention Project Regando Flores in its viability as a mechanism of restorative justice and expansion via institutionalized public policy. It concludes that programs of rehabilitation of aggressors are peaceful, restorative and efficient tools to face domestic violence against women.